Update of Genetic Diversity of Porcine Circovirus Type 2 in Chile Evidences the Emergence of PCV2d Genotype - Ariyama, Naomi; Agüero, Belén; Valdés, Valentina; Berrios, Felipe; Bucarey, Sergio; Mor, Sunil; Brito, Barbara; Neira, Victor (Frontiers in Veterinary Science, 2021)
Porcine Circovirus 2 (PCV2) can cause multiple clinical conditions known as porcine circovirus-associated diseases (PCVAD). Before the wide availability of PCV2 vaccines, PCVAD resulted in significant losses to the global swine industry. PCV2's rapid evolutionary dynamics are comparable to single-stranded RNA viruses. Thus, shifts in the dominance and distribution of different genotypes may frequently occur, resulting in the emergence and spread of varying PCV2 genotypes and recombinant strains in swine. This study aims at identifying the PCV2 genotypes currently circulating in Chile. Seven hundred thirty-eight samples were obtained from 21 swine farms between 2020 and 2021. The samples were tested using PCR for species detection and genotyping. Sequencing and phylogenetic analyses were conducted in selected samples. PCV2 was detected in 26.9% of the PCR reactions and 67% of the sampled farms. The genotypes were determined in nine farms, PCV2a in one farm, PCV2b in four, and PCV2d in five, with PCV2b and PCV2d co-circulating in one farm. The phylogenetic analysis of twelve ORF2 sequences obtained (PCV2a = 5; PCV2b = 4; PCV2d = 3) showed a PCV2a Chilean strains monophyletic cluster; closely related to Chilean viruses collected in 2012 and 2013. Of the three different PCV2b sequenced viruses, two viruses were close to the root of the PCV2b group, whereas the remaining one grouped with a South Korean virus. PCV2d sequences were closely related to Asian viruses. A previously reported PCV2a/PCV2d recombinant strain was not detected in this study. Our results suggest the emergence and potential shift to PCV2d genotype in Chilean farms.